Risk factors for parastomal hernia following abdominoperineal resection - Shang, An; Li, Liping; He, Ge; Zhuge, Donggui; Yu, Pengcheng; Xu, Junyi (Frontiers in Oncology, 2025)
ObjectiveParastomal hernia (PSH) is a common complication after stoma construction, particularly in patients with colostomy, with an incidence of up to 50%. The primary objective of the present study was to explore the clinical and radiological risk factors for the development of PSH in patients who underwent abdominoperineal resection, thereby helping surgeons identify high-risk patients and select appropriate individualized follow-up and treatment strategies.MethodsAll consecutive patients who underwent abdominoperineal resection (APR) in the left lower abdomen were considered for inclusion in the present study according to the inclusion and exclusion criteria from January 2017 to May 2022. The follow-up period of selected patients was at least 1 year. A total of 18 potential risk factors for PSH were evaluated. Univariate and multivariate binary logistic regression analyses were performed to identify factors significantly associated with PSH development. The Kaplan-Meier method was used to evaluate the association between risk factors and the cumulative incidence of PSH.ResultsIn our study, the incidence of PSH was 44.4%. In the final multivariate analysis, we identified three independent risk factors, including thickness of rectus abdominis, SAT percentage and colostomy surface area. In addition, we found that high SAT percentage (>median) and large colostomy surface area (>median) were associated with a higher three-year incidence rate than the control group (56.7% vs. 21.5% and 47.3% vs. 33.6%). However, the conclusion was opposite when the thickness of rectus abdominis was analyzed (36.7% vs. 46.2%).ConclusionIn the present study, we found that the thickness of the rectus abdominis, the SAT percentage, and the colostomy surface area were significantly associated with the development of PSH, which may be potential predictors for PSH. In particular, our study reported the potential predictive value of the thickness of rectus abdominis for the development of PSH for the first time.